Effects of co-cultivation with Gracilariopsis lemaneiformis on the explosive growth and photosynthesis of Ulva prolifera - Wei Zhou; Wentao Lu; Yi Hao; Yuyue Zhou; Yuru Yan; Qun Liu; Jiatao Xu; Juntian Xu; Chen Liang; Xincheng Song; Jiahu Xia; Jinguo Wang (PLoS ONE, 2026)
The recurring outbreak of Ulva prolifera green tides in the Yellow Sea poses a serious threat to coastal ecosystems and coastal-related industries, necessitating the development of environmentally friendly control strategies. In this study, in situ experiments were conducted using two light intensity levels and five co-cultivation biomass density combinations to investigate their effects on the growth and photosynthetic physiology of Gracilariopsis lemaneiformis and U. prolifera . The results demonstrated a significant interactive effect of light intensity and biomass density on the competitive outcome between the two species. Specifically, the relative growth rate of U. prolifera significantly decreased with increasing biomass density of G. lemaneiformis– an inhibitory effect that was particularly pronounced under high light intensity. High light enhanced the competitive suppression capacity of G. lemaneiformis , likely associated with shading effect due to its growth, while reduced photosystem stability of U. prolifera under high light further exacerbated the inhibition. Under low light, U. prolifera alleviated competitive pressure by increasing its chlorophyll content. G. lemaneiformis suppressed U. prolifera through resource competition, and a biomass density ratio of 1:4–1:6 ( U. prolifera : G. lemaneiformis ) was found to balance effective ecological control with sustained growth of G. lemaneiformis . The research findings provide novel scientific insights and empirical data to support the advancement of G. lemaneiformis aquaculture and the development of biological control strategies for mitigating green tides.